INFLUENCE OF INSTAGRAM CONTENTS TOWARDS BUYING FOOD PRODUCT INTEREST ON INSTAGRAM (A CASE STUDY OF BUYING INTEREST THROUGH PROFESSIONAL CHEF'S INSTAGRAM POST ON PRESIDENT UNIVERSITY STUDENTS) - Salsabila, Natasya Putri; Haryanto, Jony Oktavian (Research In Management and Accounting (RIMA), 2021)
Using Instagram for business activities became a specific activity among young people, especially students. One of the online businesses run by young people today was a food and beverage business, the other business was in the clothing and apparel field.  The need for food products was increasing on Instagram users who preferred to make online purchases through Instagram. The content of a professional chef's Instagram account was one that influenced individuals to buy food or beverage products through Instagram social media. Professional chef was an interesting profession known by the public and it made young people interested in becoming a professional chef as one of the career professions. Professional chefs also used Instagram media for live career promotion and branding, food product promotions, recipes and even cooking course invitations. The main subject of this research was the Instagram account of a professional chef. The research sample was 218 President University students who had Instagram accounts and made online purchases on Instagram. Data collection used was questionnaires using quantitative research methods. Validity, reliability tests, data analysis used was SEM with SmartPLS. It found that verified Instagram accounts and the intention of following updated Instagram content had influenced the purchase intention of a product, but Instagram content and users' interest in following instagram accounts did not affect the purchase intention of a product.